Ideología política en dos cuentos fantásticos de Antonio Benítez Rojo - Sardiñas Fernández, José Miguel (2022)
This article analyzes the presence of political and ideological elements in two fantastic short stories by the Cuban writer Antonio Benítez Rojo (1931-2005): “Estatuas sepultadas” and “Peligro en La Rampa” (Tute de reyes, 1967). Its purpose is to underline some rhetorical devices by means of which a fantastic fiction can get involved in a political conflict, against the general opinion about the evasive character of this literary genre. Ana Maria Barrenechea’s theory of the fantastic and Boris Uspensky’s theory of the point of view are its theoretical basis concerning the fantastic and the analysis of political and ideological components of a literary work, respectively. As a result, this study shows the presence of politic elements at a thematic level in both narratives and the way its author takes part in favor of the official discourse, despite the subtle manner of masking it through carefully chosen narrative voices.